„Ausgabe rechts am Fenster“ Zeitlichkeit und Ortsbezogenheit von Corona-Aushängen an Geschäften - Döring, Mark (Linguistik Online, 2026)
The pandemic has brought about a significant change in the semiotic landscape with signs, floor markings, and barriers during the first lockdown in Germany. In this article, pandemic-related signs at shops are analysed from a text linguistic perspective in terms of how they indicate their spatial and temporal location. For this purpose, I analysed 261 signs from Hanover regarding their references to the surrounding space and their temporality. These were then contrasted with pre-existing non-pandemic signs in the entrance area. The results show that shops usually advertise entry to their premises through architectural design and textual signs and only impose minor restrictions (e. g. opening hours). Pandemic signs temporarily suspend the associated routines of entering the shops. Informative signs establish COVID-19 as a state of emergency compared to the pre-pandemic situation. They also indicate their short-term validity via the materiality of the signs and verbal reference to specific dates. In contrast, regulatory signs indicate their short-term validity solely through their materiality. Regulatory signs combine verbal instructions and arrows to indicate new routines for using space, e. g. the new purpose for a window at a restaurant for take-away food.